Aseptic and septic prosthetic joint loosening: Impact of biomaterial wear on immune cell function, inflammation, and infection. (November 2021) - Hodges, Nicholas A.; Sussman, Eric M.; Stegemann, Jan P.
Abstract: The success of total joint replacements has led to consistent growth in the use of arthroplasty in progressively younger patients. However, more than 10 percent of patients require revision surgeries due to implant failure caused by osteolytic loosening. These failures are classified as either aseptic or septic and are associated with the presence of particulate wear debris generated by mechanical action between implant components. Aseptic loosening results from chronic inflammation caused by activation of resident immune cells in contact with implant wear debris. In contrast, septic loosening is defined by the presence of chronic infection at the implant site. However, recent findings suggest that subclinical biofilms may be overlooked when evaluating the cause of implant failure, leading to a misdiagnosis of aseptic loosening. Many of the inflammatory pathways contributing to periprosthetic joint infections are also involved in bone remodeling and resorption. In particular, wear debris is increasingly implicated in the inhibition of the innate and adaptive immune response to resolve an infection or prevent hematogenous spread. This review examines the interconnectivity of wear particle- and infection-associated mechanisms of implant loosening, as well as biomaterials-based strategies to combat infection-related osteolysis.